1998
DOI: 10.1099/0022-1317-79-8-1963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human papillomavirus type 18 (HPV-18) E6-mediated degradation of p53 in vitro and in vivo reveals significant differences based on p53 structure and cell type but little difference with respect to mutants of HPV-18 E6.

Abstract: An important characteristic of the E6 proteins derived from oncogenic associated human papillomaviruses (HPVs) is their ability to target the cellular tumour suppressor protein, p53, for ubiquitin mediated degradation. Several studies have attempted to address the important characteristics of both E6 and p53 for this activity in vitro, but the equivalent determinants have not been extensively assessed in vivo. Indeed, recent studies indicate differences between the in vitro and the in vivo degradation assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Nevertheless, viral infections may also act synergistically with environmental toxins effects. The coexistence of positive ISH and p53 over‐expression seen in 11 cases, along with four cases negative for ISH and less expressed p53 immunostaining, may be explained by the variable sensitivity of certain p53 mutants to E6 degradation and/or by tumor promotion via p53‐independent viral mechanisms such as disruption of pRb function by HPV E7 (33–36). In conjunction with recent studies, our data provide strong evidences that HPV are etiologically linked to a defined subset of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, viral infections may also act synergistically with environmental toxins effects. The coexistence of positive ISH and p53 over‐expression seen in 11 cases, along with four cases negative for ISH and less expressed p53 immunostaining, may be explained by the variable sensitivity of certain p53 mutants to E6 degradation and/or by tumor promotion via p53‐independent viral mechanisms such as disruption of pRb function by HPV E7 (33–36). In conjunction with recent studies, our data provide strong evidences that HPV are etiologically linked to a defined subset of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in vitro degradation assays do not always reflect what is happening in vivo. There are clear examples of mutants of both p53 and E6 that are defective in in vitro degradation assays but active in vivo (13,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Both HPV-16 and -18 E6 induce efficient degradation of p53 in these E6AP-null cells, and this appears to be proteasome-mediated. Obviously, previous studies have shown a central role for E6AP in the degradation of p53 Cooper et al, 2003;Hengstermann et al, 2005;Kelley et al, 2005) and there are likely to be significant differences between the in vivo assays and those performed in vitro (Gardiol and Banks, 1998;Liu et al, 1999). One E6AP-null cell line that was used in similar assays with p53 concluded that E6AP was essential for p53 degradation (Cooper et al, 2003).…”
Section: Cellsmentioning
confidence: 99%